PENERAPAN ALGORITMA REGULARIZED DISCRIMINANT ANALYSIS UNTUK KLASIFIKASI KANKER PARU - Evy Priyanti (Swabumi, 2020)
Lung cancer is a type of cancer that starts from the lungs with abnormal cell growth. Lung cancer is a type of cancer with the largest number of sufferers. In this research, Regularized Discriminant Analysis (RDA) analysis is used to classify the types of lung cancer that exist. Regularized Discriminant Analysis (RDA) is a generalization of Linear Discriminant Analysis (LDA) and Quadratic Discriminant Analysis (QDA). If the alpha parameter is set to 1, this operator performs an LDA. Likewise if the alpha parameter is set to 0, this operator performs QDA. Discriminant analysis is used to determine which variables distinguish between two or more groups that occur naturally. With an accuracy value of 60%, it can be ascertained the type of lung cancer suffered by patients for ease of care and treatment.